A source of almost pure methyl chavicol: volatile oil from the aerial parts of Tagetes lucida (Asteraceae) cultivated in Costa Rica - Cicció, José F (Revista de Biología Tropical, 2004)
The plant Tagetes lucida Cav. (syn. T. florida Sweet, T. schiedeana Less.) is an aromatic herb distributed naturally from Mexico to Honduras, at elevations between 1 000 and 2 000 m. It is used as a spice, for medicine, as insecticide and as ornamental plant. It is cultivated commercially in Costa Rica as a spice herb; it contains an oil having an anise-like odor, and the fresh aerial parts of this plant are sold in the supermarket as a substitute of tarragon (Artemisia dracunculus L.). The essential oils isolated from aerial parts bought, at May and October, in a supermarket in San José (Costa Rica). Fresh flowering aerial parts, flowers and leaves plus stems, were subjected to hydrodistillation for 3 hr using a modified Clevenger-type apparatus. The distilled oils were collected and dried over anhydrous sodium sulphate and stored in a freezer (0-10°C). The light yellow green oil yield was about 0.07% (v/w). GC/MS analyses were performed using a Shimadzu GCMS-QP5050 apparatus and CLASS 5000 software with Wiley 139 computer database. Identification of the components of the oil was performed using the retention indices, which were calculated in relation to a homologous series of hydrocarbons, and by comparison of their mass spectra with those published in the literature or those of our own database. Thirty compounds were identified, of which methyl chavicol (95-97%) was the major constituent. From flower oil, two bithienyls were detected as minor constituents.